1987
DOI: 10.1007/bf00199828
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of natural killer cytotoxicity by muramyl dipeptide and trehalose dimycolate incorporated in squalane droplets

Abstract: The effect on natural killer (NK) cytotoxicity of splenic cells from BALB/c mice pretreated i.v. with squalane-in-water preparations of muramyl dipeptide (MDP), trehalose dimycolate (TDM), or the combination of MDP-plus-TDM was investigated. MDP or TDM augmented the NK cytotoxicity which peaked 48 h after the pretreatment whereas the combination of MDP and TDM induced an inhibition of the NK activity. Infection with influenza virus, a potent stimulator of NK cells, after the pretreatment with biological respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Enhancement of NK and ADCC re-sponse was more rapid (but also more transient) in mice with constitutively weak NK activity (C57B1) than in strong reactors (CBA). Strain-related responsiveness has been recorded with MDP, a synthetic analog of peptidoglycans [14,21,23]: C57B1 mice were resistant to its stimulating effect, whereas the other strains responded. Similar kinetics of NK modulation as found by us in PGM treated CBA mice has been recently reported in DBA mice injected with MDP [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancement of NK and ADCC re-sponse was more rapid (but also more transient) in mice with constitutively weak NK activity (C57B1) than in strong reactors (CBA). Strain-related responsiveness has been recorded with MDP, a synthetic analog of peptidoglycans [14,21,23]: C57B1 mice were resistant to its stimulating effect, whereas the other strains responded. Similar kinetics of NK modulation as found by us in PGM treated CBA mice has been recently reported in DBA mice injected with MDP [13].…”
Section: Discussionmentioning
confidence: 99%
“…Since strain-related differences have been recorded whith synthetic analog of PGM, muramyl dipeptide (MDP) [14,21,23], effects of PGM were evaluated in mice with constitutively weak (C57B1) or strong (CBA, C3H) NK activity.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few reports [7][8][9][10] concerning the synthesis of a novel adamantyl-amide dipeptide that consisted of an adamantyl moiety and a dipeptide characteristic for MDP were reported. Preliminary tests showed that this compound exhibits both immunomodulating and antiviral properties in several experimental models.…”
mentioning
confidence: 99%